Germany's Foreign Policy Towards Poland and the Czech Republic - Cordell, Karl; Wolff, Stefan (Taylor & Francis, 2005)
This is a new exploration of how the events of the twentieth century still cast a shadow over relations between Germany, Poland and the Czech Republic. Using social constructivism theory, it provides a comparative assessment of Germany's post-reunification relations with the Czech Republic and Poland within the framework of the contemporary alliance structure. Identifying the key actors and factors, Cordell and Wolff examine the long-standing continuity in the norms and values that underpin German foreign policy and explore the issues of borders, territory, identities, minorities and population transfers. Paying particular attention to the process of European integration and the role of the new Germany within Europe, the authors identify how new possibilities for co-operation might finally overcome legacies of the past. This pioneering study will be of particular interest to students of European politics and international studies.
English
Keywords: Politics & government; Political structure & processes; Diplomacy; sudeten; germans; relations; munich; agreement; minority; government; expellee; organizations; polish